Penggunaan Dana Desa Berdasarkan Undang-Undang Nomor 6 Tahun 2014 tentang Desa, di Desa Mandungo dan Desa Denduka, Kecamatan Wewewa Selatan, Kabupaten Sumba Barat Daya - Martinus Bili; Saryono Yohanes; Cyrilius Lamataro (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Law No. 6/2014 provides a legal basis for the allocation of village funds in Indonesia with the aim of improving the welfare of rural communities through infrastructure development, local economic empowerment, and improved quality of life. However, the use of village funds is often in the spotlight due to potential misuse, lack of transparency, and low accountability. This research aims to find out how far the village government functions and the obstacles in the use of village funds based on Law No. 6 of 2014 in Mandungo Village and Denduka Village, South Wewewa District, Southwest Sumba Regency. This research method uses a qualitative approach with data collection techniques through interviews, observation, and document analysis. The results showed that although both villages have relatively complete government structures in accordance with the Village Law, the functions of village government have not been fully optimized. Some village government functions, such as the preparation of village regulations, financial management, and public services still face significant challenges. In addition, barriers to the use of village funds were also found, including a lack of transparency, a lack of administrative capacity, and a lack of community understanding of village fund allocations. This study concludes that despite the existence of regulations governing village governance functions and the management of village funds, their implementation still faces significant challenges.